Learner-Centred Pedagogy in the Global South Pupils and Teachers' Experiences - Sakata, Nozomi (Routledge Research in International and Comparative Education, 2023)
Learner-Centred Pedagogy in the Global South: Pupils and Teachers' Experiences shines light on learner-centred pedagogy (LCP), which has gained popularity within global and national governments, albeit resulting in puzzling and inconsequential appropriation. Nozomi Sakata draws on award-winning research on learner centred pedagogy conducted in Tanzania that looks to shift the focus from teachers and teaching to students and learning. The recent spread of LCP through global policy discourse meets Tanzania's historical and contemporary (in)compatibility in local schools. The book explores how pupils' perceived classroom experiences are formed through pedagogical elements beyond the classroom. It also enquires into how observable LCP activities and/or pupils' perceptions of classroom practices relate to their academic performance and learning attitudes. The book highlights the multidimensionality of pedagogy and the need to consider multiple viewpoints from both teachers and pupils and to consider the historical and socio-cultural contexts in any pedagogical research. This book will be of value to researchers and students interested in pedagogy, policy transfer and education reforms in the global South. The Chapters 5, 6 and 8 of this book are available for free in PDF format as Open Access from the individual product page at www.routledge.com. It has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives 4.0 license.